The history and future of correctional psychology - Magaletta, Philip R. (Springer, 2023)
Part I Early Pioneers -- 1 Correctional Psychology Pioneer: William Thomas Root, Jr. (1882-1945) -- 2 "Correctional Psychology Pioneer: Edgar A. Doll (1889–1968) -- 3 Correction Psychology Pioneer: F. Lovell Bixby (1901-1975) -- 4 Correctional Psychology Pioneer: Asher Pacht (1922-2017) -- 5 Correctional Psychology Pioneer: Marguerite Warren (1920-2008) -- Part II Growth and development -- 6 Correctional Therapeutic Communities -- 7 Criminal Thinking -- 8 "Revitalizing the Lost Scrolls of Correctional Bible: Before the Risk-Need-Responsivity Model" -- 9 Correctional Education and Job Preparation as a Correctional Psychology Service: A Three Era’s Approach -- Part III The future of correctional psychology -- 10 Incarcerated while Transgender -- 11 Medications for Opioid Use Disorder (MOUDs): What Psychology Service Providers Should Know to Improve Correctional Care -- 12 Correctional Psychology and Technology: Past, Present and Future.-13 "The Future of Violence Prevention and Reduction: Making Better Use of Correctional Psychology Practices " -- 14 Envisioning the Future of Correctional Psychology: Administration, Training, Practice and Research.